2019
DOI: 10.1021/acs.biomac.9b01053
|View full text |Cite
|
Sign up to set email alerts
|

Polyampholytes as Emerging Macromolecular Cryoprotectants

Abstract: Cellular cryopreservation is a platform technology which underpins cell biology, biochemistry, biomaterials, diagnostics, and the cold chain for emerging cell-based therapies. This technique relies on effective methods for banking and shipping to avoid the need for continuous cell culture. The most common method to achieve cryopreservation is to use large volumes of organic solvent cryoprotective agents which can promote either a vitreous (ice free) phase or dehydrate and protect the cells. These methods are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 94 publications
2
79
0
Order By: Relevance
“…On the other hand, because DMSO is a cell-permeable cryoprotectant and considered to exert its cryoprotective effect both intra-and extracellularly, non-cellpermeable ZIL theoretically cannot completely replace DMSO. Therefore, ZIL may adequately dehydrate the cells to prevent intracellular ice formation like other non-cell-permeable cryoprotectants [20][21][22] . It is also reported that non-cell-permeable cryoprotectants can exert their efficacy by stabilising the plasma membranes 23,24 ; however, it is totally unclear at this stage whether ZIL has similar effect as these non-cell-permeable cryoprotectants.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, because DMSO is a cell-permeable cryoprotectant and considered to exert its cryoprotective effect both intra-and extracellularly, non-cellpermeable ZIL theoretically cannot completely replace DMSO. Therefore, ZIL may adequately dehydrate the cells to prevent intracellular ice formation like other non-cell-permeable cryoprotectants [20][21][22] . It is also reported that non-cell-permeable cryoprotectants can exert their efficacy by stabilising the plasma membranes 23,24 ; however, it is totally unclear at this stage whether ZIL has similar effect as these non-cell-permeable cryoprotectants.…”
Section: Resultsmentioning
confidence: 99%
“…These two factors are especially crucial when assessing new macromolecular cryoprotectants which may function by different mechanisms (compared to conventional CPAs) and result in unanticipated stresses (or protection). 9 For example, Stöver and co-workers reported polyampholytes for DMSO-free cryopreservation; 38 cell viabilities immediately post-thaw were similar to that of 10% DMSO, but the cells did not adhere well, and post-thaw growth curves suggested the polymer did not produce viable cells unless additional DMSO was added. Matsumura used vitrification (using 6.5 M ethylene glycol) for mesenchymal stromal (stem) cell cryopreservation with added polyampholytes.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these issues AFP mimics such as Poly(vinyl alcohol) (PVA) have been used for animal cell 17 and bacteria 15 cryopreservation as biocompatible alternatives endued with IRI properties. Complex carbohydrates such as hydroxyethyl starch (HES) 18,19 , alginate [20][21][22] or synthetic polyampholytes 23 have been adopted in the field of cell cryopreservation either with other pCPAs or alone. More radical solutions have also been proposed such as the use of metal-organic frameworks, 24 armors around cells to prevent damage by ice crystals or hydroxyapatite nanoparticles, 13 as vehicles to promote the internalization of CPAs.…”
Section: Introductionmentioning
confidence: 99%